Reducing the Threat of Electrical Hazards through the Application of Solar Energy: Realizing Child-Friendly Electricity in Elementary Schools. - sutoyo, sutoyo; Yudhanto, Ferriawan (Jurnal Engine: Energi, Manufaktur, dan Material, 2023)
The advancement of information technology provides ease of learning. However, learning media in schools usually depends on average electrical settings and electronic devices to support information technology (IT). The learning media in Indonesia generally depends on the utilization of PLN's electrical energy. It is undeniable that electricity is a basic need in teaching and learning activities today, even though the existence of electrical installations in the midst of children saves dangers that need to be anticipated. The solution is to provide socialization and education on child-friendly technology. In this case, the school community will be introduced to utilizing and building safe electrical installations for children. In principle, some electrical components available on the market will have their own level of safety, and safe and child-friendly components must be chosen. Furthermore, electrical installations will be built with solar energy sources because the technology has many advantages, including renewable energy, without high-voltage cable networks, and providing efficiency in school operational costs. It is more important that solar electricity can work at low voltages to be safe in children's environments. The result at the activity location installed electricity from Solar Power Plant with a 300 Watt inverter to provide electricity for school computer devices. In addition, 10 outdoor lighting points are installed that are set to turn on and off automatically. The main goal to provide efficient and safe electrical facilities for children has been well realized.